In 1926 : living at the edge of time - Gumbrecht, Hans Ulrich (Harvard University Press, 1997)
In this thoroughly innovative work, Hans Ulrich Gumbrecht evokes the year 1926 through explorations of such things as bars, boxing, movie palaces, hunger artists, airplanes, hair gel, bullfighting, film stardom and dance crazes. From the vantage points of Berlin, Buenos Aires, and New York, the reader is allowed multiple itineraries, ultimately becoming immersed in the activities, entertainments, and thought patterns of the citizens of 1926.